Binding sites of salivary statherin for Porphyromonas gingivalis recombinant fimbrillin. - Amano, A (1996)
We investigated the binding sites of salivary statherin involved in the interaction with Porphyromonas gingivalis recombinant fimbrillin (r-Fim). Synthetic peptides representing statherin analogs were used to localize the binding domains of statherin. Peptide F4 (residues 29 to 43) significantly bound to r-Fim and inhibited r-Fim binding to statherin-coated hydroxyapatite beads. Successive peptides in which pairs of amino acid residues were deleted starting at the N terminus of peptide F4 were synthesized. Peptide N1 without Leu-29-Tyr-30 had significantly reduced direct binding and inhibition ability. The deletions of residues 31 to 40 had little effect on interaction with r-Fim. The tripeptide N6 representing Tyr-41-Thr-42-Phe-43 retained significant binding to r-Fim. Another set of peptides was synthesized by deleting individual amino acid residues from the C and N termini of peptide F4 to identify functional residues among the five putative functional residues 29, 30, and 41 to 43. Peptide C1 missing Phe-43 lost over 50% of its binding ability. Binding ability was gradually reduced with deletions from the peptides. Peptide C5 (amino acids 31 to 40) weakly affected direct binding and inhibition. Collectively, the results of this study suggests that Leu-29-Tyr-30 and Tyr-41-Thr-42-Phe-43 are important binding regions that mediate the binding of statherin to P. gingivalis fimbrillin.